Metabolic Insight of Neutrophils in Health and Disease - Kumar, Sachin; Dikshit, Madhu (Frontiers in Immunology, 2019)
Neutrophils are the most abundant, short lived, and terminally differentiated leukocytes with distinct tiers of arsenals to counter pathogens. Neutrophils were traditionally considered transcriptionally inactive cells, but recent researches in the field led to a paradigm shift in neutrophil biology and revealed subpopulation heterogeneity, and functions pivotal to immunity and inflammation. Furthermore, recent unfolding of metabolic plasticity in neutrophils has challenged the long-standing concept of their sole dependence on glycolytic pathway. Metabolic adaptations and distinct regulations have been identified which are critical for neutrophil differentiation and functions. The metabolic reprogramming of neutrophils by inflammatory mediators or during pathologies such as sepsis, diabetes, glucose-6-phosphate dehydrogenase deficiency, glycogen storage diseases, systemic lupus erythematosus, rheumatoid arthritis, and cancer are now being explored. In this review, we discuss recent developments in understanding of the metabolic regulation, that may provide clues for better management and newer therapeutic opportunities for neutrophil centric immuno-deficiencies and inflammatory disorders.